Energy efficiency optimization for downlink OFDMA system in heterogeneous network with QoS constraints. (10th April 2015) - Bastos, Joaquim; Huq, Kazi Mohammed Saidul; Mumtaz, Shahid; Rodriguez, Jonathan; Verikoukis, Christos
Summary: Energy efficiency (EE) has currently turn into one of the major issues in heterogeneous networks (HetNet) paradigm of today's wireless communication industry. In this paper, we optimize EE for downlink OFDMA system in HetNet, taking into account realistic network power consumption model, that is, considering circuit power. This paper investigates the EE maximization using convex optimization theory where primary optimization criterion is data rate in a downlink multiuser HetNet. Given QoS (data rate) requirement, for maximizing EE, a constrained based optimization problem is devised. Because the optimization problem is non‐convex in nature, we reconstruct the optimization problem as a convex one and devise a pragmatically efficient novel resource assignment algorithm for maximizing achievable EE, with quick convergence. The considered optimization problem is transformed into a convex optimization problem by redefining the constraint using cubic inequality, which results in an efficient iterative resource allocation algorithm. In each iteration, the transformed problem is solved by using dual decomposition with a projected gradient method. Analytical insights and numerical results exhibit the potency of the devised scheme for the targeted complex wireless systems. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Energy efficiency (EE) has currently turned into one of the major issues in Heterogeneous Networks paradigm of today's wireless communication industry. Consequently, achieving high EE is turning out to be a prime concern for designing of the future wireless communications paradigm. Energy saving is predominantly positioning itself at the forefront of system design, as operators look to increase EE, that is, bits per Joule.